Stigma, social support, and depression among people living with HIV in Thailand - Li, Li (2009)
BACKGROUND: People living with HIV/AIDS (PLWHA) in Thailand face tremendous challenges, including HIV-related stigma, lack of social support, and mental health issues such as depression. This study aims to examine complex relationships among demographics, HIV-related stigma, and social support and their impact on depression among PLWHA in Thailand. METHODS: This study uses data collected in northern and northeastern Thailand. A total of 408 PLWHA were recruited and interviewed in 2007. HIV-related stigma was measured by two subscales: “Internalized Shame” and “Perceived Stigma.” Based on correlation analyses, hierarchical multiple regression models were used to examine the predictors of depression, social support, and HIV-related stigma, controlling for demographic characteristics. RESULTS: Correlational analysis revealed that depression was significantly associated with both dimensions of stigma: internalized shame and perceived stigma. Self-reported emotional social support was negatively associated with depression. We found that internalized shame and emotional social support were significant predictors of depression after controlling for gender, age, income, and education. CONCLUSIONS: HIV-related stigma has a negative impact on psychological wellbeing of PLWHA in Thailand, and emotional social support remains a protective factor against depression. Intervention developers and clinicians working with PLWHA may find it useful to incorporate the association between stigma and depression into their programs and treatments, and to address social support as a protective effect for the mental health of PLWHA.